Analisis Usaha Penangkapan Ikan dengan Kapal Purse Seine Pasca Moratorium di Pelabuhan Perikanan Samudera Kendari - Kartono Kartono; Ayub M. Padangaran; Ine Fausayana (Universitas Halu Oleo, 2019)
The study was carried out at the Pelabuhan Perikanan Samudera (PPS) in Kendari. The study aims to analyze the income and feasibility as well as the growth rate of fishing business using mini purse seine vessels after the moratorium. The study period was 2 months, namely July and August 2019. The population in this study was the mini purse seine ship business unit, amounting to 61. The samples were determined using the simple random sampling method with a sample size of 20 ship business units or 30 percent of the population. The data collected includes: fishing costs, fish production for one year, and the average price of fish production received by fishermen. Data analysis was performed using the formula for income and revenue-cost ratio (R / C). The results of the study show that the temporary suspension policy (moratorium) on permits for foreign and ex-foreign fishing vessels has an impact on increasing the catch of local fishermen. The fishing business using mini purse seine vessels at PPS Kendari is feasible to be continued with the value of R/C = 1.79. The growth rate of the mini purse seine ship business after the moratorium has fluctuated but is showing a good sign.Keywords: moratorium; capture fisheries business; purse seine ship